The American Kestrel (Falco sparverius) genoscape: implications for monitoring, management, and subspecies boundaries. Issue 2 (24th April 2021) - Ruegg, Kristen C; Brinkmeyer, Michaela; Bossu, Christen M; Bay, Rachael A; Anderson, Eric C; Boal, Clint W; Dawson, Russell D; Eschenbauch, Amber; McClure, Christopher J W; Miller, Karl E; Morrow, Lance; Morrow, Jill; et al.
Abstract: Identifying population genetic structure is useful for inferring evolutionary process and comparing the resulting structure with subspecies boundaries can aid in species management. The American Kestrel ( Falco sparverius ) is a widespread and highly diverse species with 17 total subspecies, only 2 of which are found north of U.S./Mexico border ( F. s. paulus is restricted to southeastern United States, while F. s. sparverius breeds across the remainder of the U.S. and Canadian distribution). In many parts of their U.S. and Canadian range, American Kestrels have been declining, but it has been difficult to interpret demographic trends without a clearer understanding of gene flow among populations. Here we sequence the first American Kestrel genome and scan the genome of 197 individuals from 12 sampling locations across the United States and Canada in order to identify population structure. To validate signatures of population structure and fill in sampling gaps across the U.S. and Canadian range, we screened 192 outlier loci in an additional 376 samples from 34 sampling locations. Overall, our analyses support the existence of 5 genetically distinct populations of American Kestrels—eastern, western, Texas, Florida, and Alaska. Interestingly, we found that while our genome-wide genetic data support the existence of previously described subspecies boundaries in the United States and Canada, genetic differences across the sampled range correlate more with putative migratory phenotypes (resident, long-distance, and short-distance migrants) rather than a priori described subspecies boundaries per se. Based on our results, we suggest the resulting 5 genetically distinct populations serve as the foundation for American Kestrel conservation and management in the face of future threats. Lay Summary: The American Kestrel ( Falco sparverius ) is a widespread iconic raptor species that has shown highly variable trends in abundance over the last several decades. Here we sequence the first American Kestrel genome and scan the genome for genetic variation in order to identify five genetically distinct populations across the U.S. and Canadian breeding range. The resulting map of genetic variation (the genoscape) can serve as a foundation for testing hypotheses to explain observed population-specific responses to climate change and other stressors.